Growth and physiological responses of banana (Musa spp.) under different levels of salinity and organic fertilizer in the Northern Sultanate of Oman - Al Harthy, Khalid Mubarak Saleh (2019)
Salinity is a major hazard facing banana production in arid regions in the Sultanate of Oman, reducing production up to 50 % when exceeded threshold level of >1.0 dS m- 1. Three split-plot experiments were conducted in Malaysia and Sultanate of Oman – one was conducted to evaluate the degree of tolerance to four salinity levels (0.17 (control), 3.0, 6.0 and 9.0 dS m- 1) on growth, physiological and biochemical parameters of Diwan, FHIA18, Malindi and Williams cultivars under Malaysia’s environment. Two other experiments, conducted in the Sultanate of Oman, examined three salinity levels (0.45, 3.0 and 6.0 dS m-1) on same parameters on Malindi and Somali cultivars. The third experiment assessed responses of the same cultivars supplemented with 7.0 and 14.0 kg chicken manure as soil amendments. Results showed that salinity levels yielded in significant reduction in number of leaves, pseudostem height, girth and average leaf area. Measured parameters decreased in the range of 20.8% to 14.6%, 8.2% to 4.9%, 36.08% to 12.1% and 53.7% to 53.7% respectively. Higher salinity levels caused reductions in photosynthetic and chlorophyll pigments, and secondary metabolic compounds. The reduction was significant when soil was ameliorated with 14.0 kg chicken manure compared to 7.0 kg treatment. Reduction in chlorophyll pigments suggests decrease of photosynthesis components at 6.0 and 9.0 dS m-1 salinity levels. The average reduction in Chl-a, Chl- b, total Chl, photosynthesis rate (PN), stomata conductance (gs) and transpiration rate (E) were 59.7 %, 43.3 %, 38.3 %, 22.6 %, 62.3 %, 55.8 % respectively. The addition of 7.0 kg of chicken manure gave more positive effects than 14.0 kg treatment on morphological and physiological parameters. All cultivars were observed to be sensitive to salinity, but Malindi and FHIA18 were more tolerant in terms of Chl-a (13.4, 10.2 mg cm-2 FW), Chl-b (7.5 and 5.6 mg cm-2 FW), and total chlorophyll than Diwan and Willimas. Total proline content (PRLN) decreased by 11% compared to 34.3 % and by 25.8 % for treatments with the addition of chicken manure. Salinity henolic (TPC), total flavonoid (TFC) and ferric reducing antioxidant power assay (FRAP) except FRAP under arid environment. Reduction was significant in K+/Na+ and Ca+/Na+ ratios with increasing levels of salinity from a total of 33.3 % and 77.9 % in banana leaves, 94.7 and 57.5 % in banana pseudostem, 94.9 and 87.1 % in roots, respectively. The study observed that higher salinity increased K+/Na+ ratios. Malindi accumulated higher ratio compared to Somali. Ca+/Na+ ratio increased leaf and pseudostem by 28.9 % and 165.9% respectively at 9.0 dS m-1 salinity, but decreased by 14.7 % in leaf at 6 dS m-1 and by 10.7 % and 40.6% in rhizome and roots at 9.0 dS m-1. Based on morphological, physiological and chemicals parameters, Malindi and FHIA18 showed similar performances in terms of vegetative growth and tolerance at higher salinity levels. Further investigation on responses at molecular levels and yield features would be relevant in future research for banana cultivation in regions of arid environment.